Rationale, secondary outcome scores and 1-year follow-up of a randomised trial of platelet-rich plasma injections in acute hamstring muscle injury: the Dutch Hamstring Injection Therapy study. Issue 18 (4th May 2015) - Reurink, Gustaaf; Goudswaard, Gert Jan; Moen, Maarten H; Weir, Adam; Verhaar, Jan A N; Bierma-Zeinstra, Sita M A; Maas, Mario; Tol, Johannes L
Abstract : Background: Platelet-rich plasma (PRP) injections are an experimental treatment for acute muscle injuries. We examined whether PRP injections would accelerate return to play after hamstring injury. The methods and the primary outcome measure were published in the New England Journal of Medicine ( NEJM ) as 'Platelet-rich plasma injections in acute muscle injury' (2014). This article shares information not available in the NEJM letter or online supplement, especially the rationale behind the study and the secondary outcome measures including 1 year re-injury data. Methods: We performed a multicentre, randomised, double-blind, placebo-controlled trial in 80 competitive and recreational athletes with acute hamstring muscle injuries. Details can be found in the NEJM (http://www.nejm.org/doi/full/10.1056/NEJMc1402340 ). The primary outcome measure was the time needed to return to play during 6 months of follow-up. Not previously reported secondary outcome scores included re-injury at 1 year, alteration in clinical and MRI parameters, subjective patient satisfaction and the hamstring outcome score. Results: In the earlier NEJM publication, we reported that PRP did not accelerate return to play; nor did we find a difference in the 2-month re-injury rate. We report no significant between-group difference in the 1-year re-injury rate (HR=0.89; 95% CI, 0.38 to 2.13; p=0.80) or any other secondary outcome measure. Conclusions: At 1-year postinjection, we found no benefit of intramuscular PRP compared with placebo injections in patients with acute hamstring injuries in the time to return to play, re-injury rate and alterations of subjective, clinical or MRI measures.